IMPACT CHARACTERISTICS OF COMBINED TUBE EXPANSION-AXIAL SPLITTING IMPACT ABSORPTION MODULE - Dipajaya Nugraha, Arya
The need for impact energy-absorbing modules in the application of structural crashworthiness is essential. Various alternatives of energy absorbing mechanism based on plastic deformation are presented by numerous investigators, since 1970s until recently, with various application, particularly for vehicles. Some of the more popular mechanisms include progressive buckling, multi-cells, tube inversion, tube expansion, and axial splitting. The main idea of this thesis is to assess the present mechanism that combines two of the most effective plastic energy-absorbing mechanisms, i.e., tube inversion and axial splitting. Each mechanism provides nearly ideal behaviour of flat force versus displacement characteristics but with its respective drawbacks. The previous mechanism has less stroke efficiency, whilst the latter has relatively low response force, hence absorbed relatively less energy. By combining the two mechanisms, it is hoped to overcome the drawbacks of each mechanism. However, further research is still needed to answer these problems: relationships between geometry parameters and impact characteristics, design boundaries to prevent undesired modes of failure, and behaviour towards varying impact velocity. This research, specifically utilizes numerical and analytical approaches, validated with experiment. The finite element model was deemed valid with average error value of 2.38% for Pm, 3.67% for Ppeak, and 5.38% for SEA. Mathematical model to predict Pm and SEA for the combined module was generated through response surface modelling. The equations state Pm as the function of expansion ratio, thickness ratio, and initial diameter whilst SEA as the function of expansion ratio. Through the parametric analysis, design envelope for the present mechanism has been established, i.e. the expansion ratio shall not be greater than 1.235 to prevent premature splitting and the thickness ratio of the present module shall be in the range of 20 to min ,,,,,,,,,,,,,........................................................................................................,,